Optomechanically-generated photon–phonon single pairs with both discrete- and continuous-variable entanglements. (2nd February 2022) - Yu, Cun; Yang, Zhenshan; Meng, Xiangguo; Zhang, Zhentao; Zhang, Xia; Bai, Chenglin
Abstract: By exploiting two mechanical modes in an optomechanical resonator, photon–phonon single pairs with both discrete- and continuous-variable entanglements can be generated in a waveguide that is coupled to the resonator. The discrete- and continuous-variable entanglements in the photon–phonon pair can be independently controlled via adjusting the central frequency and spectral width of the input optical pump, respectively.